Measuring Preferred Store Satisfaction Using Consumer Choice Criteria as a Mediating Factor - Hutcheson, Graeme D.; Moutinho, Luiz (Journal of marketing management, 1998)
This paper attempts to model the causal effect that consumers' perception of choice criteria used to determine supermarket patronage has on the levels of perceived satisfaction with a preferred store. A factor analysis was used to determine distinct constructs regarding choice behaviour and a regression analysis was applied to the data to determine the extent of the relationship between perceived importance of the constructs and the level of satisfaction felt by the respondents. Six distinct factors were derived from the data to account for store choice. A combination of two of the factors, the "quality of produce and staff" and the occurrence of low prices and the frequency of special promotions" were particularly important in determining store choice and were also significantly related to levels of satisfaction felt by respondents for their preferred store. The implications of these results are discussed and recommendations for further development of the model are made.